Conflict and resolution the ethics of forgiveness, revenge, and punishment - Satne, Paula; Scheiter, Krisanna M. (Springer, 2022)
Given the current climate of political division and global conflict it is not surprising that there has been an increasing interest in how we ought to respond to perceived wrongdoing, both personal and political. In this volume, top scholars from around the world contribute all new original essays on the ethics of forgiveness, revenge, and punishment. This book draws on both historical and contemporary debates in order to answer important questions about the nature of forgiveness, the power of apology, the relationship between punishment and revenge, the path to reconciliation, the morality of blame, and the role of forgiveness in political conflict.The chapter "Remembrance beyond Forgiveness" is available open access under a Creative Commons Attribution 4.0 International License via link.springer.com.
Keywords: Religion and Philosophy; Moral Philosophy and Applied Ethics; Ethik, Moralphilosophie; B; Ethics; Sozialphilosophie, Politische Philosophie; Moral Philosophy; Political Philosophy; Hardcover, Softcover / Philosophie/Allgemeines, Lexika; Political sciencePhilosophy; Aufsatzsammlung